Soluble epoxide hydrolase inhibition alleviates chemotherapy induced neuropathic pain - Takeshita, Ashley A.; Hammock, Bruce D.; Wagner, Karen M. (Frontiers in Pain Research, 2023)
Chemotherapy induced peripheral neuropathy (CIPN) is a particularly pernicious form of neuropathy and the associated pain is the primary dose-limiting factor of life-prolonging chemotherapy treatment. The prevalence of CIPN is high and can last long after treatment has been stopped. Currently, late in the COVID-19 pandemic, there are still increased psychological pressures on cancer patients as well as additional challenges in providing analgesia for them. These include the risks of nonsteroidal anti-inflammatory drug (NSAID) analgesics potentially masking early infection symptoms and the immunosuppression of steroidal and opiate based approaches. Even without these concerns, CIPN is often inadequately treated with few therapies that offer significant pain relief. The experiments we report use soluble epoxide hydrolase inhibitors (sEHI) which relieved this intractable pain in preclinical models. Doses of EC5026, an IND candidate intended to treat neuropathic pain, elicited dose dependent analgesic responses in multiple models including platinum-based, taxane, and vinca alkaloid-based CIPN pain in Sprague Dawley rats. At the same time as a class, the sEHI are known to result in fewer debilitating side effects of other analgesics, likely due to their novel mechanism of action. Overall, the observed dose-dependent analgesia in both male and female rats across multiple models of chemotherapy induced neuropathic pain holds promise as a useful tool when translated to the clinic.